2007
DOI: 10.1086/509920
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes Infection from Foods Prepared in a Commercial Establishment: A Case-Control Study of Potential Sources of Sporadic Illness in the United States

Abstract: Most cases of L. monocytogenes infection were not associated with outbreaks. Reducing the burden of foodborne listeriosis may require interventions directed at retail environments and at foods, such as melons and hummus, that are not commonly recognized as high risk. Because of the severity of listeriosis, pregnant women and other persons at risk may wish to avoid eating these newly implicated foods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
93
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 31 publications
2
93
0
2
Order By: Relevance
“…36%) of sporadic cases (17). Our analysis of the 136 serotype 4b isolates from sporadic human listeriosis in the United States in the 2003-to-2008 period showed that the known epidemic clones were responsible for over one-half of the sporadic cases and were continuously causing listeriosis during this period.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…36%) of sporadic cases (17). Our analysis of the 136 serotype 4b isolates from sporadic human listeriosis in the United States in the 2003-to-2008 period showed that the known epidemic clones were responsible for over one-half of the sporadic cases and were continuously causing listeriosis during this period.…”
Section: Discussionmentioning
confidence: 77%
“…36%) (8,17). However, our understanding of the population structure of L. monocytogenes serotype 4b from sporadic listeriosis in the United States remains severely limited.…”
mentioning
confidence: 99%
“…Strains of certain serotypes (1/2a, 1/2b, and 4b) are responsible for the majority (over 95%) of human clinical cases (3,4). Serotype 4b strains have been implicated in numerous outbreaks and in a significant portion of sporadic cases (4,5). Three serotype 4b clonal groups (ECI, ECII, and ECIa [also designated ECIV]) have been responsible for multiple outbreaks (6).…”
mentioning
confidence: 99%
“…Significant higher estimated incidences were seen for serotypes I 4, [5],12:i:-(75% higher; 95% CI=24% to 147%) and Newport (28% higher; 95% CI=5% to 55%). …”
Section: Modeled 2007mentioning
confidence: 90%